(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
On a patient with installed dental implants and having a system of implant-abutment connections using a fixing screw, the microbiological landscape of the oral cavity was studied in the dynamics of observation with and without the transition of the platform to the abutment. All patients were divided into 2 groups: group 1 consisted of 9 patients with an implant-abutment system without switches; 2 group made up 10 schemes with the transition of the platform to the abutment. The material for the microbiological study was a biomaterial from the soft tissue mucosa around the abutment. The study of the dynamics of the microbial flora in patients with the transition of the platform to the abutment relative to the indicators before prosthetics, showing a decrease in the quantitative indicators of the representatives of both its stabilizing and aggressive components.